The impact of social organizations on HIV/AIDS prevention knowledge among migrants in Hefei, China - Wenting Wang; Ren Chen; Ying Ma; Xuehui Sun; Xia Qin; Zhi Hu (BMC, 2018)
Abstract Background There is a growing recognition of the need to provide HIV/AIDS prevention and care to migrant workers. Social involvement, a type of social capital, is considered a 'critical enabler' of effective HIV/AIDS prevention. Designated participation in formal community groups by the government (e.g., political parties) and informal, voluntary local networks by NGOs (e.g., alumni association, cultural & sports club) play different roles in HIV prevention. The objective of this study is to assess the impact of different types of social organizations on HIV/AIDS prevention knowledge among migrant workers. Methods A cross-sectional study of 758 migrants was conducted in Hefei, Anhui Province, China. Data were collected through a self-reported questionnaire. Logistic regression was used to assess associations between different social organizations and HIV/AIDS prevention. Results Migrants who participated in social organizations had a higher awareness of HIV/AIDS knowledge than migrants who do not participate in social organizations. Higher levels of HIV/AIDS knowledge is associated with positive HIV/AIDS behaviors for people who attended political parties (odds ratio [OR] = 3.49, 95% CI: 1.22-9.99). This effect is not significant for alumni association. For both political parties and alumni association members (OR = 0.19, 95% CI: 0.06-0.66, OR = 0.20, 95% CI: 0.08-0.61, respectively), people who exhibited higher levels of HIV/AIDS knowledge had more negative attitudes than those with less knowledge. Conclusion Social organizations play an important role in improving HIV/AIDS knowledge and behavior in migrants, providing a great opportunity for HIV/AIDS prevention.